2015
DOI: 10.3109/07434618.2015.1126636
|View full text |Cite
|
Sign up to set email alerts
|

Operational Demands of AAC Mobile Technology Applications on Programming Vocabulary and Engagement During Professional and Child Interactions

Abstract: Typically, the vocabulary in augmentative and alternative communication (AAC) technologies is pre-programmed by manufacturers or by parents and professionals outside of daily interactions. Because vocabulary needs are difficult to predict, young children who use aided AAC often do not have access to vocabulary concepts as the need and interest arises in their daily interactions, limiting their vocabulary acquisition and use. Ideally, parents and professionals would be able to add vocabulary to AAC technologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…The easier-to-program VSD app increased the number of VSDs and vocabulary programmed, and increased the number of child communicative exchanges. 28 In the second study, strategies to increase GPSbased access to vocabulary were identified. 29 Overall, these studies provide evidence for the use of consumer level technology to provide JIT supports to individuals with ASD.…”
Section: Just-in-time Support and Autism Spectrum Disordermentioning
confidence: 99%
“…The easier-to-program VSD app increased the number of VSDs and vocabulary programmed, and increased the number of child communicative exchanges. 28 In the second study, strategies to increase GPSbased access to vocabulary were identified. 29 Overall, these studies provide evidence for the use of consumer level technology to provide JIT supports to individuals with ASD.…”
Section: Just-in-time Support and Autism Spectrum Disordermentioning
confidence: 99%
“…This technology allows the user to build their own repertoire of sentences for communication according to their day-to-day needs. Caron et al (2016) argued that the same is not true for systems with recorded audio capabilities, as sentences for communication are usually preprogrammed by manufacturers, parents, or professionals outside the daily communication interactions. In this manner, the user could find it difficult to express their actual communication needs.…”
Section: Discussionmentioning
confidence: 99%
“…The START! Strategy (Bhana et al, 2019; Caron et al, 2016) detailed in Figure 2 provides a step-by-step guide on how to transform traditional storybooks into interactive VSDs.…”
Section: Vsds and Shared Storybook Readingmentioning
confidence: 99%